2014
DOI: 10.1074/jbc.m114.591461
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine Aminotransferase III and Glutamine Transaminase L Are Identical Enzymes that have Cysteine S-Conjugate β-Lyase Activity and Can Transaminate l-Selenomethionine

Abstract: Background: KAT I and GT-Kidney (K) are identical enzymes that ␤-eliminate and transaminate Se-methyl-L-selenocysteine (MSC). Results: KAT III and GT-Liver (L) are identical and metabolize L-selenomethionine (SM). Conclusion: MSC and SM are transaminated to seleno-keto acids, recognized HDAC inhibitors, by KAT/GT enzymes. Significance: Anticancer efficacy of MSC and SM depends in part on tissue expression of KAT/GT enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 60 publications
(63 reference statements)
0
46
0
Order By: Relevance
“…No significant inhibition of MSC transamination was noted in the presence of 1 mM glutamine. Even in the presence of 100 mM glutamine the rate of transamination of MSC was~20 % that observed for the control that lacked added glutamine [5]. This finding is significant because it is unlikely that all potential amino acid competitive inhibitors of GTK in the cell added together can reach a combined concentration of 100 mM.…”
Section: Possible Role Of Glutamine Transaminases In Chemopreventive mentioning
confidence: 85%
See 4 more Smart Citations
“…No significant inhibition of MSC transamination was noted in the presence of 1 mM glutamine. Even in the presence of 100 mM glutamine the rate of transamination of MSC was~20 % that observed for the control that lacked added glutamine [5]. This finding is significant because it is unlikely that all potential amino acid competitive inhibitors of GTK in the cell added together can reach a combined concentration of 100 mM.…”
Section: Possible Role Of Glutamine Transaminases In Chemopreventive mentioning
confidence: 85%
“…K cat /K m values for the next six "best" amino acid substrates, namely histidine, methionine, phenylalanine, asparagine, cysteine, and kynurenine, were reported to be 171, 162, 147, 126, 114, and 92 min −1 mM −1 , respectively. We have shown that KAT III is identical to GTL [5]. Inasmuch as (a) GTK and GTL were described prior to the identification of KAT I and KAT III as distinct kynurenine aminotransferases, (b) glutamine is a better substrate than is kynurenine, (c) mammalian tissues contain far more glutamine than kynurenine, and (d) the present chapter focuses on glutamine, we have assumed the nomenclature GTK and GTL throughout the present chapter, except where it is necessary to indicate the KAT nomenclature often presented in basic scientific literature.…”
Section: Mammalian Tissues Contain At Least Three Aminotransferases Tmentioning
confidence: 94%
See 3 more Smart Citations